Modifications of chemical functional groups of Pandanus amaryllifolius Roxb and its effect towards biosorption of heavy metals - Abdullah, M.Z. (American Institute of Physics Inc., 2015)
The utilization of non-living biomass as an alternative biosorbent for heavy metal removal has gain a tremendous consideration through the years. Pandanus amaryllifolius Roxb or pandan leaves, which is widely used as food additives in the South East Asia region, has been selected for its viability in the said effort due to the presence of chemical functional groups on its cellular network that enables the sorption to occur. In order to elucidate the possible mechanisms participated during the heavy metal removal process, the biosorbent undergone a series of modification techniques to alter the chemical functional groups present on its constituent. From the outcome of the chemically-modified biosorbent being subjected to the contact with metal cations, nitrogen- and oxygen-containing groups present on the biosorbent are believed to be responsible for the metal uptake to occur through complexation mechanism. Modifying amine groups causes 14 reduction of Cu(II) uptake, whereas removing protein element increases the uptake to 26 as compared to the unmodified biosorbent. Also, scanning electron micrographs further suggested that the adsorption mechanism could perform in parallel, as attributed to the evidence of porous structure throughout the biosorbent fibrous nature. Â© 2015 AIP Publishing LLC.